The Role of Emergency Generator during Black-Out on the MV. Kelud: Peranan Emergency Generator saat Black-Out di Kapal KM. Kelud - Utomo, Muhamad Nurji Setyo; Wiweko, Albert; Siregar, Muhammad Sapril; David, Muhammad; Nurmala, Eka (ALTAIR: Jurnal Transportasi dan Bahari, 2024)
Emergency generator is an auxiliary machine that functions to generate electrical power to meet the electrical needs of the ship during an emergency (black-out). This research was conducted to find out what caused the black-out onboard KM. Kelud, how the role of the Emergency generator during a black-out, and how to maintain the emergency generator so that it is always ready when used. The research method that the author uses is a qualitative research method. Data collection is done through interviews and observations. The results obtained from this study indicate that the cause of the black-out on KM. Kelud is the entry of mud into the hull, causing the cooling system in the main engine to be disrupted and eventually black-out. The role of the emergency generator during a black-out is as a temporary source of electricity to run several devices, such as navigation equipment, ship lighting, fire alarm systems, sprinkle pumps, and watertight door systems. In order for the emergency generator to run according to its function, it must be carried out routine maintenance such as checking batteries, oil and lubricants, cooling systems, and periodic testing.